Econometric analysis of carbon markets the European Union emissions trading scheme and the clean development mechanism - Chevallier, Julien. (Springer)
Through analysis of the European Union Emissions Trading Scheme (EU ETS) and the Clean Development Mechanism (CDM), this book demonstrates how to use a variety of econometric techniques to analyze the evolving and expanding carbon markets sphere, techniques that can be extrapolated to the worldwide marketplace. It features stylized facts about carbon markets from an economics perspective, as well as covering key aspects of pricing strategies, risk and portfolio management.   Aimed at those with a basic understanding of time series econometrics, this book will be extremely useful for researchers and working professionals (trading managers, energy and commodity traders, quantitative analysts, consultants, utilities), and especially those in econometrics and carbon finance. The material is also appropriate for students (advanced undergraduates, MSc, MBA) in the field of econometrics, energy and environmental economics. Readers are supplied with hyperlinks to data and R computer codes, while instructors receive problem sets, a solutions manual, and presentation slides. 1. Introduction to emissions trading -- 2. CO2 Price fundamentals -- 3. Link with the macroeconomy -- 4. The clean development mechanism -- 5. Risk-hedging strategies and portfolio management -- 6. Advanced topics: time-to-maturity and modeling the volatility of carbon prices -- Solutions -- Index.